Evaluación Integrada de pensamiento crítico y conciencia ciudadana como competencias ATC21s en Costa Rica y en Japón - Mena Araya, Aarón Elí (Universidad de Costa Rica, 2022)
Competency-based learning in elementary education requires the integrated instruction of multiple competencies. Because of its inherent complexity, the assessment of such instruction poses significant challenges. This study presents the results of instructional and assessment experiences implemented in elementary schools of Costa Rica and Japan during the 2019 school year. These activities aimed at developing ATC21s competencies related to local and global citizenship, critical thinking, and ICT literacy. In each country, an experimental group (26 students in Costa Rica and 27 in Japan) participated in two learning units that incorporated animated shorts, graphic organizers, and comics to address community issues. The results from both units are assessed through the analysis of comics and questionnaires. Control groups (25 students in Costa Rica and 27 in Japan) participated only in the questionnaires, which focused on concepts related to community and citizen participation. The comics’ analysis focused on the participants’ citizens self-awareness and critical thinking skills. The questionnaires’ analysis dealt with attitudes related to community and citizen participation. In Costa Rica, the analysis of the comics showed significant increases in critical thinking (PPC) and citizen self-awareness (PCC) scores in the second unit. In both units, Japanese students showed better performance in PPC and PCC than their Costa Rican peers. In both countries, correlations were found between PPC and PCC. The analysis of the questionnaires did not show conclusive results in either country. These results suggest that narrative is more suitable than description and exposition for students to express active and critical attitudes related to citizenship and democracy.